(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The study examined the efficacy of aloe extract in the topical application of zoonotic leishmaniasis. To date, specific drug prevention of leishmaniasis has not been developed. One of the important problems in dermatology is the search for effective, low-toxic agents and methods of therapy for cutaneous leishmaniasis, since the drugs used have cardio-, hepato-, and nephrotoxicity.